p53-associated metabolic checkpoint regulation in a tick embryo-derived cell line - Bruno Moraes; Angélica Arcanjo; Tomohiro Okagawa; Cintia Nogueira; Antonia Brumana; Juliana L. Souza; Ariana A. Vasconcelos; Fabio C.L. Almeida; Kamila Guimarães Pinto; Alessandra Filardy; Robson Q. Monteiro; Satoru Konnai; et al. (Insect Biochemistry and Molecular Biology, 2026)

Thermokinetic, Thermodynamic, and Pyrolysis Analysis of Agro-Industrial Biomass for Bioenergy: Insights from Isoconversional Models and Neural Networks - Marcelo L. Cocco; Edilton N. Silva; Jamilson Silva; Thais L. C. Gomes; Lucas Meili; Gercílio A. Almeida; Robson C. Sousa (BioEnergy Research, 2026)
The growing demand for renewable energy and sustainable waste management has driven interest in the thermochemical valorization of agro-industrial residues. This study investigated the thermokinetic, thermodynamic, and pyrolysis behavior of four lignocellulosic biomasses—coconut shell, orange pomace, banana pseudostem, and compost barn—for bioenergy applications. Thermogravimetric analysis (TG/DSC) and kinetic modeling using isoconversional methods and multilayer perceptron (MLP) neural networks were employed. Kinetic, pyrolysis, and thermal parameters—pre-exponential factor, activation energy, reaction order, initial devolatilization and devolatilization completion temperatures — were determined, along with thermodynamic parameters such as entropy (ΔS), Gibbs free energy (ΔG), and enthalpy (ΔH). All biomasses exhibited typical lignocellulosic degradation profiles, with predominant exothermic events. Activation energy varied widely (140.32–458.35 kJ·mol⁻¹), with banana pseudostem showing the lowest values, indicating easier energy conversion. Banana pseudostem exhibited the highest thermal decomposition index (2.84 × 10 − 6 %²·min⁻²·°C⁻³) and the lowest initial devolatilization temperature (183.70 °C). Orange pomace showed the highest ΔH (892 kJ·mol⁻¹) and ΔS (1.31 kJ·mol⁻¹·K⁻¹), suggesting high thermal stability. ΔG values remained relatively constant across conversion degrees. MLP neural networks demonstrated superior performance ( R² = 0.99) compared to traditional models in predicting TG curves. These findings support the efficient selection and modeling of biomass for thermal processes and reinforce the potential of AI-based tools in optimizing bioenergy applications.

Mitigating overload conditions in vibrating screens through fuzzy-controlled feed rate regulation - Alexandre G. Fonseca; Robson A. Duarte; Kaike S. Albuquerque; Thomás Pinto; Thiago A.M. Euzébio (Minerals Engineering, 2026)

Genomic Insights into a New Burkholderia cenocepacia Sequence Type Linked to Cepacia Syndrome in Cystic Fibrosis - Tatiane S. Xavier; Felipe A. Simão; Heloisa S. Rosa; Jade C. S. Colomer; Renata W. Cohen; Tânia W. Folescu; Ana Paula D’A. Carvalho-Assef; Robson S. Leão; Elizabeth A. Marques (Current Microbiology, 2026)
Burkholderia cenocepacia is an important pathogen in cystic fibrosis (CF) patients, responsible for chronic lung infections and, in severe cases, cepacia syndrome (CS), characterized by necrotizing pneumonia, bacteremia, and high mortality. Epidemic lineages, such as B. cenocepacia J2315 (ET12) and ST32, are highly transmissible and frequently associated with CS. In this study, five B. cenocepacia isolates recovered from sputum and blood samples of a pediatric CF patient who developed CS were sequenced and analyzed in silico using multilocus sequence typing (MLST), phylogenomics, genomic similarity metrics, and comparative genomics to identify virulence determinants, resistance genes, and mobile genetic elements. A novel sequence type (ST2424), not associated with any known clonal complex, was identified. Phylogenomic analysis revealed high genetic relatedness among the isolates, consistent with a monoclonal infection undergoing within-host microevolution. Comparative analyses revealed distinct genetic profiles: aaiB (T6SS) was present in all isolates, whereas narG and manCcore were exclusive to bloodstream isolates. Acquired resistance determinants, including bla OXA−1043 , sul1 , aac(6′)-IIc , and aadA1 , were detected and were absent from the reference strains B. cenocepacia J2315 and ST32. Mobile genetic elements, including insertion sequences from the IS3, IS5, and IS200/IS605 families, as well as a putatively conjugative plasmid encoding Tra/Trb subunits of the type IV secretion system, were also identified. These findings describe a novel B. cenocepacia sequence type associated with fatal CS and highlight the high genomic plasticity of this species, reinforcing the importance of genomic surveillance to detect emerging variants and improve clinical management in CF.

The nonpeptide angiotensin-(1–7) mimic AVE0991 attenuates neuroendocrine and behavioral responses to chronic unpredictable stress - Maria Luiza Antunes Fonseca; Laura Beatriz de Oliveira Amaral; Sthéfanie C. A. Gonçalves; Laura A. Costa; Laura Barroso Ferreira de Oliveira; Flávio A. G. Mourão; Marco Antônio Peliky Fontes; Michael Bader; Robson A. S. Santos; Maria José Campagnole-Santos; Lucas M. Kangussu (Psychopharmacology, 2026)
Rationale Chronic stress, frequently associated with dysfunction of the hypothalamic–pituitary–adrenal (HPA) axis and reduced neuroplasticity, is a major risk factor for psychiatric disorders such as anxiety and depression. Objective The present study aimed to validate a 21-day chronic unpredictable stress (CUS) model and to investigate the effects of the Mas receptor agonist AVE0991 on stress-induced behavioral and molecular alterations. Methods Male C57BL/6J mice were exposed to a 21-day CUS protocol. Animals were randomly assigned to four groups: control + saline, CUS + saline, control + AVE0991, and CUS + AVE0991 (3 mg/kg, i.p .). AVE was administered daily during the last two weeks of the stress protocol. Behavioral tests were performed to evaluate anxiety- and depressive-like behaviors, and plasma corticosterone, blood glucose levels, and brain-derived neurotrophic factor (BDNF) levels in the prefrontal cortex, hippocampus, and hypothalamus were measured. Results CUS exposure significantly increased plasma corticosterone and glucose levels and induced anxiety- and depressive-like behaviors. Stressed animals also showed reduced BDNF levels in the prefrontal cortex, hippocampus, and hypothalamus. Treatment with AVE0991 attenuated the increase in corticosterone and prevented stress-induced hyperglycemia. Moreover, AVE0991 reduced depressive-like behavior, increased latency to immobility, and improved anxiety-related parameters in the elevated plus maze and open field tests without affecting locomotor activity. AVE0991 also prevented the reduction of BDNF levels in stress-exposed animals. Conclusion These findings validate the CUS model and demonstrate that activation of the Mas receptor by AVE0991 exerts anxiolytic, antidepressant, and neuroprotective effects, supporting its potential as a therapeutic strategy for stress-related neuropsychiatric disorders.

Coat characteristics, physiological traits, serum metabolites, and thyroid hormones of Canindé and Moxotó goats in a semiarid environment - Wallace S. Tavares da Silva; Robson M. Freitas Silveira; Jacinara H. Gurgel Morais Leite; Concepta McManus; Débora A. Evangelista Façanha (Tropical Animal Health and Production, 2026)
This study evaluated the adaptive responses of dark-coated Canindé and light-coated Moxotó goats reared under semiarid conditions in Brazilian semiarid through an integrated assessment of thermoregulatory, biochemical, hormonal, and morphological variables. Sixty non-pregnant and non-lactating goats (30 Canindé and 30 Moxotó) were evaluated during summer and winter under the same grazing and management conditions. Animals received native pasture and concentrate supplementation (200 g/head/day). Significant breed × season interactions ( P < 0.05) were observed for physiological, metabolic, hormonal, and coat variables. Dark-coated Canindé goats showed higher coat surface temperature and greater seasonal variation in coat thickness (0.60 vs. 0.51 mm), as well as marked seasonal changes in T4 (1.67 vs. 4.47 µg/dL), glucose (48.87 vs. 105.03 mg/dL), and albumin (4.42 vs. 8.19 mg/dL) from summer to winter, indicating greater metabolic flexibility. In contrast, light-coated Moxotó goats maintained lower and more stable thyroid hormone concentrations across seasons (T4: 1.63 vs. 1.63 µg/dL) and exhibited increased creatinine levels during winter (0.95 vs. 1.57 mg/dL), suggesting a more conservative adaptive strategy. Multivariate analyses demonstrated distinct adaptive profiles between breeds. Factor analysis revealed integration between thermoregulation and metabolism in Canindé goats, whereas Moxotó goats showed stronger biochemical compensation mechanisms. Decision tree analysis identified globulin and coat thickness as the main discriminating variables between breeds and seasons. These findings demonstrate that locally adapted goat breeds use distinct but effective adaptive strategies to cope with semiarid environmental conditions and provide important phenotypic indicators to support conservation programs, breed selection, and climate-resilient small ruminant production systems.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

The improved auxin signalling via entire mutation enhances aluminium tolerance in tomato - Regiane K.G. Silva; João Antonio Siqueira; Willian Batista-Silva; Marcelle Ferreira Silva; Thiago Wakin; Jonas Rafael Vargas; Gabriel Vilela; Robson Ribeiro; Domingos F.M. Neto; Aristea A. Azevedo; Cleberson Ribeiro; Alisdair R. Fernie; et al. (Plant Science, 2026)

Distance Transform Loss: Boundary-aware segmentation of seismic data - Rafael Henrique Vareto; Ricardo Szczerbacki; Luiz A. Lima; Pedro O.S. Vaz-de-Melo; William Robson Schwartz (Computers & Geosciences, 2026)

Multifunctional glycerol-derived porous carbons bearing C-P(O)- and/or C-S-bonded functionalities: Nanoarchitectonics and application potential through a novel H3PO4-driven route - Paulo H.L. Pinheiro; Robson M. da Silva; Claudio T. Carvalho; Magno A.G. Trindade; Wagner A. Carvalho; Gabriela T.M. Xavier; Raphael Rodrigues (Biomass and Bioenergy, 2026)

Fish metacommunity dynamics in an intermittent river of Northeast Brazil: ecological drivers and conservation implications - Leonardo Oliveira-Silva; Silvia Yasmin Lustosa-Costa; Robson da Costa Tamar Ramos; Bráulio A. Santos; Telton Pedro Anselmo Ramos (Journal for Nature Conservation, 2026)

Mas Knockout Mice Present Altered Behavioral and Neuroendocrine Coping Responses to Chronic Unpredictable Stress - Sthéfanie C. A. Gonçalves; Andressa da Silveira Silva; Bruna Karen Oliveira Nogueira; Flávio A. G. Mourão; Marco Antônio Peliky Fontes; Michael Bader; Robson A. S. Santos; Maria José Campagnole-Santos; Lucas M. Kangussu (Molecular Neurobiology, 2026)
Stress is defined as a disruption of homeostasis that elicits adaptive responses aimed at restoring physiological balance. However, when stress becomes chronic or overwhelming, maladaptive changes may occur, contributing to endocrine, behavioral, and neuropsychiatric dysfunctions. Beyond the classical neuroendocrine axes, such as the sympatho-adrenomedullary and hypothalamic–pituitary–adrenal (HPA) axes, the renin-angiotensin system has also being implicated in stress modulation. Previous studies have shown that angiotensin-(1–7), acting through its receptor Mas, exerts a modulatory effect on the stress response, attenuating anxiety- and depression-like behaviors induced by various stressors. Here we investigated the impact of genetic deletion of Mas on the consequences of chronic unpredictable stress (CUS) exposure. Over 21 consecutive days, mice were subjected to random stressors, after which endocrine, behavioral and neurochemical assessments were performed. Mas knockout (KO) mice exposed to CUS exhibited significantly elevated corticosterone and blood glucose levels compared to stressed wild-type mice. In behavioral tests, stressed Mas KO mice displayed the highest immobility times in the forced swimming test, indicating enhanced depressive-like behavior. Anxiety-like behavior was also heightened in Mas KO mice, as evidenced by a significant reduction in the percentage of time spent in the open arms of the elevated plus maze test. Neurochemical analysis revealed a marked reduction in brain-derived neurotrophic factor (BDNF) levels in key brain regions of stressed Mas KO animals. Together, these findings suggest that Mas plays a critical role in the neurobiology of stress, since its absence exacerbates HPA axis hyperactivity, depression- and anxiety-like behaviors, as well as BDNF reduction. Overall, these results highlight the potential neuroprotective role of Mas in stress-related disorders.

Leveraging pre-trained computer vision models for accurate classification of meat freshness - Marcelo M. Hidalgo; Robson C. Lima; Elisabete A. De Nadai Fernandes; Márcio A. Bacchi; Gabriel A. Sarriés (Food Chemistry, 2025)

Hidden diversity revealed by DNA barcoding of paralichthyidae fish along the caribbean and brazilian coast - Leandro A. Argôlo; Robson T. C. Ramos; Jamille A. Bitencourt; José Henrique Galdino; Iracilda Sampaio; Paulo R. A. M. Affonso (Genetica, 2025)

Coat traits, skin evaporation, and milk production of Majorera and Palmera goats in a temperate region - Wallace S. T. da Silva; Robson Mateus Freitas Silveira; Wilma E. da Silva; Jacinara H. G. M. Leite; Luis A. Bermejo; Concepta McManus; Alexandr T. Krupij; Débora A. E. Façanha (International Journal of Biometeorology, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

The role of the P2X7 receptor in inactivated SARS-CoV-2-induced lung injury - N. C. Carvalho-Barbosa; Fabiana Cristina-Rodrigues; Jairo R. Temerozo; Thiago M. L. Souza; Andre L. Gouvêa; Claudio A. Canetti; Eleonora Kurtenbach; Dumith Chequer Bou-Habib; Claudia F. Benjamim; Christina M. Takiya; Luiz E. B. Savio; Robson Coutinho-Silva (Purinergic Signalling, 2025)

Genomic and phenotypic insights into Serratia interaction with plants from an ecological perspective - Ubiana C. Mourão Silva; Daliane R. C. da Silva; Sara Cuadros-Orellana; Leandro M. Moreira; Laura R. Leite; Julliane D. Medeiros; Erica B. Felestrino; Washington L. Caneschi; Nalvo F. Almeida; Robson S. Silva; Christiane A. Oliveira-Paiva; Vera Lúcia dos Santos (Brazilian Journal of Microbiology, 2025)

Biogeographical Origins of Caatinga Squamata Fauna - Castiele Holanda Bezerra; Antonio Rafael Lima Ramos; João Fabrício Mota Rodrigues; Fernanda A. S. Cassemiro; Robson Waldemar Ávila (Journal of Biogeography, 2025)
Aim Several lines of evidence have noted that open vegetation biomes in the Neotropics are younger than moist forests, leading us to question which historical processes shaped the current species distribution patterns in these new biome formations. Here we investigate the temporal patterns of speciation and colonisation from surrounding biomes (Amazonia, Atlantic Forest and Cerrado) in the Caatinga historical assembly of squamate species, to understand the role of geomorphological events and climate change in driving its diversification. Location Neotropics. Taxon Squamata (snakes, lizards and amphisbaenians). Methods We used a phylogenetic tree and occurrence data for 459 squamate species distributed throughout four different biomes (Amazonia, Atlantic Forest, Cerrado and Caatinga) to reconstruct ancestral geographic ranges using the R package BioGeoBEARS. We used BAMM to estimate the rates of species diversification. Results Our results indicate that the current diversity patterns of squamates in the Caatinga were a result of pervasive faunal exchanges from adjacent biomes since the Paleogene, with similar numbers of dispersal events in each source area. The Neogene period was determinant in the diversification process, leading to the current assembly patterns of this group in the Caatinga. Main Conclusions The landscape transformation and climate change that increased aridity in northeastern Brazil probably shaped the diversification of dry‐adapted squamates in the Caatinga, like tropidurid lizards. However, the Pleistocene climatic fluctuations associated with the highly heterogeneous gradients of topography, geology, soils, climatic conditions, and different vegetation physiognomies could have facilitated faunal exchange with their neighbouring forested biomes, explaining the current presence of some typical forested lineages inside the Caatinga domain and help us to clarify the current distribution patterns of squamates in this region.

Evaluation of three serological tests for the diagnosis of Brucella suis in dogs using Bayesian latent class analysis - Catherine C. Kneipp; Ronald Coilparampil; Mark Westman; Monica Suann; Jennifer Robson; Simon M. Firestone; Richard Malik; Siobhan M. Mor; Mark A. Stevenson; Anke K. Wiethoelter (Preventive Veterinary Medicine, 2024)

Examining Food Security, Fruit and Vegetable Intake, and Cardiovascular Disease Risk Outcomes of Produce Prescription (PPR) Programs: A Systematic Review - Zoe Harper; Adriana Verdezoto Alvarado; Sarah E. Katz; Alisha J. Rovner; Elizabeth Anderson Steeves; Hollie A. Raynor; Shannon M. Robson (Journal of Nutrition Education and Behavior, 2024)

Angiotensin-(1–7) decreases inflammation and lung damage caused by betacoronavirus infection in mice - Erick Bryan de Sousa Lima; Antônio Felipe S. Carvalho; Isabella Zaidan; Adelson Héric A. Monteiro; Camila Cardoso; Edvaldo S. Lara; Fernanda S. Carneiro; Leonardo C. Oliveira; Filipe Resende; Felipe Rocha da Silva Santos; Luiz Pedro Souza-Costa; Ian de Meira Chaves; et al. (Inflammation Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Difference in Dietary Behaviors Between Children with and Without Neurodevelopmental Disabilities: Results from the 2022 National Survey of Children’s Health - S. Robson; L. Krott; C. Baker-Smith; A. Bhat; F. Patterson; B. Brewer (Journal of the Academy of Nutrition and Dietetics, 2024)

Investigation of the 2010 rock avalanche onto the regenerated glacier Brenndalsbreen, Norway - Siri H. Engen; Marthe Gjerde; Thomas Scheiber; Gernot Seier; Hallgeir Elvehøy; Jakob Abermann; Atle Nesje; Stefan Winkler; Kristine F. Haualand; Denise C. Rüther; Alexander Maschler; Benjamin A. Robson; et al. (Landslides, 2024)
Rock avalanches onto glaciers are rare in Norway. Here, we examine a rock avalanche that spread onto the regenerated Brenndalsbreen, an outlet glacier from Jostedalsbreen ice cap. The rock avalanche is intriguing in that limited information exists with respect to the exact time of failure, location of detachment area, and preparatory and triggering processes. Based on an analysis of ice stratigraphy and photographic documentation, we assess that the event happened between mid-March and June 4, 2010. A potential triggering factor could have been heavy snow and rainfall combined with above freezing air temperatures on March 18–19, 2010. We use digital terrain models to determine that the detachment area is at an almost vertical rock slope in a narrow gorge above Lower Brenndalsbreen. The deposit volume is estimated to 0.130 ± 0.065 Mm 3 , and the H / L ratio and fahrböschung are 0.45 and 24°, respectively. We apply a Voellmy flow model to confirm the detachment location and volume estimate by producing realistic runout lengths. Although glacial debuttressing may have been a likely preparatory process, the detachment area was exposed for 45–70 years before the rock avalanche occurred. The supraglacial rock avalanche debris was separated into two branches with a distinct melt-out line across the glacier. The debris reached the glacier front in 2019 and 2020, where it started being deposited proglacially while Lower Brenndalsbreen kept receding. The 2010 Brenndalsbreen rock avalanche may not be a unique event, as deposits constituting evidence of an old rock avalanche are currently melting out at the glacier front.

Genomic Comparative of Pseudomonas aeruginosa Small Colony Variant, Mucoid and Non-mucoid Phenotypes Obtained from a Patient with Cystic Fibrosis During Respiratory Exacerbations - Mila M. Almeida; Leonardo R. Bastos; Mônica C. Firmida; Rodolpho M. Albano; Elizabeth A. Marques; Robson S. Leão (Current Microbiology, 2024)

Respiro-fermentative behavior of two yeasts in melon musts - Tiago J.S. Coelho; Solange Sousa; Leonardo A.F. Pascoal; Max R. Quirino; Gilsandro A. Costa; Fernando A. Santos; Robson R.P. Coelho (Food Bioscience, 2024)

Chromosomal structural rearrangements implicate long non-coding RNAs in rare germline disorders - Rebecca E. Andersen; Ibrahim F. Alkuraya; Abna Ajeesh; Tyler Sakamoto; Elijah L. Mena; Sami S. Amr; Hila Romi; Margaret A. Kenna; Caroline D. Robson; Ellen S. Wilch; Katarena Nalbandian; Raul Piña-Aguilar; et al. (Human Genetics, 2024)
In recent years, there has been increased focus on exploring the role the non-protein-coding genome plays in Mendelian disorders. One class of particular interest is long non-coding RNAs (lncRNAs), which has recently been implicated in the regulation of diverse molecular processes. However, because lncRNAs do not encode protein, there is uncertainty regarding what constitutes a pathogenic lncRNA variant, and thus annotating such elements is challenging. The Developmental Genome Anatomy Project (DGAP) and similar projects recruit individuals with apparently balanced chromosomal abnormalities (BCAs) that disrupt or dysregulate genes in order to annotate the human genome. We hypothesized that rearrangements disrupting lncRNAs could be the underlying genetic etiology for the phenotypes of a subset of these individuals. Thus, we assessed 279 cases with BCAs and selected 191 cases with simple BCAs (breakpoints at only two genomic locations) for further analysis of lncRNA disruptions. From these, we identified 66 cases in which the chromosomal rearrangements directly disrupt lncRNAs. In 30 cases, no genes of any other class aside from lncRNAs are directly disrupted, consistent with the hypothesis that lncRNA disruptions could underly the phenotypes of these individuals. Strikingly, the lncRNAs MEF2C-AS1 and ENSG00000257522 are each disrupted in two unrelated cases. Furthermore, we experimentally tested the lncRNAs TBX2-AS1 and MEF2C-AS1 and found that knockdown of these lncRNAs resulted in decreased expression of the neighboring transcription factors TBX2 and MEF2C , respectively. To showcase the power of this genomic approach for annotating lncRNAs, here we focus on clinical reports and genetic analysis of seven individuals with likely developmental etiologies due to lncRNA disruptions.

Genetic determinants of antimicrobial resistance in polymyxin B resistant Pseudomonas aeruginosa isolated from airways of patients with cystic fibrosis - Felipe A. Simão; Mila M. Almeida; Heloísa S. Rosa; Elizabeth A. Marques; Robson S. Leão (Brazilian Journal of Microbiology, 2024)

Adapting the Marine Stewardship Council risk-based framework to estimate impacts on seabirds, marine mammals, marine turtles and sea snakes - Stephanie D. Good; Kate Dewar; Polly Burns; Keith Sainsbury; Richard A. Phillips; Bryan P. Wallace; Caterina Fortuna; Vinay Udyawer; Bruce Robson; Edward F. Melvin; Rohan J.C. Currey (Marine Policy, 2024)

Forecasting carrot yield with optimal timing of Sentinel 2 image acquisition - L. A. Suarez; M. Robertson-Dean; J. Brinkhoff; A. Robson (Precision Agriculture, 2024)
Accurate, non-destructive forecasting of carrot yield is difficult due to its subterranean growing habit. Furthermore, the timing of forecasting usually occurs when the crop is mature, limiting the opportunity to implement alternative management decisions to improve yield (during the growing season). This study aims to improve the accuracy of carrot yield forecasting by exploring time series and multivariate approaches. Using Sentinel-2 satellite imagery in three Australian vegetable regions, we established a time series of carrot phenological stages (PhS) from ‘days after sowing’ (DAS) to enhance prediction timing. Numerous vegetation indices (VIs) were analyzed to derive temporal growth patterns. Correlations with yield at different PhS were established. Although the average root yield (t ha −1 ) did not significantly differ across the regions, the temporal VI signatures, indicating different regional crop growth trends, did vary as well as the PhS at when the maximum correlation with yield occurred ( $$PhS_{{R2_{max} }} )$$ P h S R 2 max ) with two of the regions producing a delayed $$PhS_{{R2_{max} }}$$ P h S R 2 max (i.e. 90–130 DAS). The best multivariate model was identified at 70 DAS, extending the forecasting window before harvest between 20 to 60 days. The performance of this model was validated with new crops producing an average error of 16.9 t ha −1 (27% of total yield). These results demonstrate the potential of the model at such early stage under varying growing conditions offering growers and stakeholders the chance to optimize farming practices, make informed decisions on selling, harvesting, and labor planning, and adopt precision agriculture methods.

Small-bodied mammal diversity facets vary discretely across an understudied ecotone in the western Amazon-Cerrado - Robson Flores de Oliveira; Manoel dos Santos-Filho; Ana Filipa Palmeirim; Juliano A. Bogoni (Mammalian Biology, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Improving the knowledge management of marine megafauna strandings - Bruno S.S.P. Oliveira; Robson G. Santos; Bráulio A. Santos (Journal of Environmental Management, 2024)

Experimental and Theoretical Investigation of the Effect of Cellulose Nanowhiskers on the Pb(II) Adsorption by Superabsorbent Hydrogel Nanocomposites - André R. Fajardo; Robson S. Oliboni; Carlos E. C. de Magalhães; Maria G. M. Chaves; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2024)

Glycerol-based H3PO4-activated carbon as a versatile adsorbent for removal of pollutants from wastewater: A novel synthesis protocol - Iveth A. da Silva; Liriana M. Roveda; Claudio T. Carvalho; Magno A.G. Trindade; Robson M. da Silva; Raphael Rodrigues (Environmental Nanotechnology, Monitoring & Management, 2023)

Applying biorefinery concepts for sugarcane straw upcycling using alkaline and enzymatic treatments to produce value-added compounds and bioenergy - Robson Tramontina; Eupídio Scopel; Lívia Brenelli; Guilherme P. Nogueira; Telma T. Franco; Camila A. Rezende; Rosana Goldbeck; Fabio M. Squina (Biomass and Bioenergy, 2023)

Severe simplification of the structure of dung beetle assemblages in neotropical soybean croplands regardless of the native vegetation domain - Anildo Ferreira Machado; Ricardo José da Silva; César Murilo de Albuquerque Correa; Robson dos Santos Alves da Silva; Fernando Zagury Vaz-de-Mello; Mônica Josene Barbosa Pereira; Carlos A. Peres; Dionei José da Silva; Danielle Storck-Tonon (Agriculture, Ecosystems & Environment, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Using climate reanalysis and remote sensing-derived data to create the basis for predicting the occurrence of algal blooms, harmful algal blooms and toxic events in Santa Catarina, Brazil - Luiz F.N. Vianna; Robson V. de Souza; Mathias A. Schramm; Thiago P. Alves (Science of The Total Environment, 2023)

Physiological properties of the visual system in the Green Weaver ant, Oecophylla smaragdina - Yuri Ogawa; Lochlan Jones; Laura A. Ryan; Simon K. A. Robson; Nathan S. Hart; Ajay Narendra (Journal of Comparative Physiology A, 2023)
The Green Weaver ants, Oecophylla smaragdina are iconic animals known for their extreme cooperative behaviour where they bridge gaps by linking to each other to build living chains. They are visually oriented animals, build chains towards closer targets, use celestial compass cues for navigation and are visual predators. Here, we describe their visual sensory capacity. The major workers of O. smaragdina have more ommatidia (804) in each eye compared to minor workers (508), but the facet diameters are comparable between both castes. We measured the impulse responses of the compound eye and found their response duration (42 ms) was similar to that seen in other slow-moving ants. We determined the flicker fusion frequency of the compound eye at the brightest light intensity to be 132 Hz, which is relatively fast for a walking insect suggesting the visual system is well suited for a diurnal lifestyle. Using pattern-electroretinography we identified the compound eye has a spatial resolving power of 0.5 cycles deg −1 and reached peak contrast sensitivity of 2.9 (35% Michelson contrast threshold) at 0.05 cycles deg −1 . We discuss the relationship of spatial resolution and contrast sensitivity, with number of ommatidia and size of the lens.

Organic selenium supplementation on metabolic profile of dairy goats - Angela Maria de Vasconcelos; Marcelo R. de Carvalho Rios; Thays P. Martins; Joice M. Bonfim; Yara A. Magalhães; Raymundo R. Pinheiro; Marcos Cláudio P. Rogério; Débora Andréa E. Façanha; Josiel Ferreira; Robson Mateus Freitas Silveira (Tropical Animal Health and Production, 2023)

Correction to: Coupled climate response to Atlantic Multidecadal Variability in a multi-model multi-resolution ensemble - Daniel L. R. Hodson; Pierre-Antoine Bretonnière; Christophe Cassou; Paolo Davini; Nicholas P. Klingaman; Katja Lohmann; Jorge Lopez-Parages; Marta Martín-Rey; Marie-Pierre Moine; Paul-Arthur Monerie; Dian A. Putrasahan; Christopher D. Roberts; et al. (Climate Dynamics, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Saponite-inspired Materials as Remediation Technologies for Water Treatment: an Overview - Dihêgo Henrique L. Damacena; Pollyana Trigueiro; Victor Hugo Monteiro; Luzia Maria C. Honorio; Thiago Marinho Duarte; Robson Cunha; Marcelo B. Furtini; Maria Gardennia Fonseca; Edson C da Silva-Filho; Josy A. Osajima (Environmental Processes, 2023)

Hybridization and genetic characterization of sea turtles in Alagoas, northeastern Brazil - João P. F. A. Almeida; Oscar K. L. Marques; Tamí Mott; Robson G. Santos (Marine Biology, 2023)

Rotational horse grazing and dry weather maximize infiltration into soil macropores - Laura B. Kenny; Daniel Giménez; Joshua S. Caplan; Ali Al-Sarraji; Mohson AlHello; Mark G. Robson; William Meyer; Carey A. Williams (Soil and Tillage Research, 2023)

Phylogenetic relationships and the origin of New World soles (Teleostei: Pleuronectiformes: Achiridae): The role of estuarine habitats - Jamille A. Bitencourt; Paulo R.A.M. Affonso; Robson T.C. Ramos; Horacio Schneider; Iracilda Sampaio (Molecular Phylogenetics and Evolution, 2023)

Pneumocoelomogram as a novel negative contrast diagnostic imaging technique to evaluate coelomic organs in bearded dragons (Pogona vitticeps) - Garrett A. Fraess; Robson F. Giglio; Nicole I. Stacy; Sarah Crevasse; James F.X. Wellehan; Amy B. Alexander (Journal of Exotic Pet Medicine, 2023)

Coupled climate response to Atlantic Multidecadal Variability in a multi-model multi-resolution ensemble - Daniel L. R. Hodson; Pierre-Antoine Bretonnière; Christophe Cassou; Paolo Davini; Nicholas P. Klingaman; Katja Lohmann; Jorge Lopez-Parages; Marta Martín-Rey; Marie-Pierre Moine; Paul-Arthur Monerie; Dian A. Putrasahan; Christopher D. Roberts; et al. (Climate Dynamics, 2022)
North Atlantic sea surface temperatures (SSTs) underwent pronounced multidecadal variability during the twentieth and early twenty-first century. We examine the impacts of this Atlantic Multidecadal Variability (AMV), also referred to as the Atlantic Multidecadal Oscillation (AMO), on climate in an ensemble of five coupled climate models at both low and high spatial resolution. We use a SST nudging scheme specified by the Coupled Model Intercomparision Project’s Decadal Climate Prediction Project Component C (CMIP6 DCPP-C) to impose a persistent positive/negative phase of the AMV in the North Atlantic in coupled model simulations; SSTs are free to evolve outside this region. The large-scale seasonal mean response to the positive AMV involves widespread warming over Eurasia and the Americas, with a pattern of cooling over the Pacific Ocean similar to the Pacific Decadal Oscillation (PDO), together with a northward displacement of the inter-tropical convergence zone (ITCZ). The accompanying changes in global atmospheric circulation lead to widespread changes in precipitation. We use Analysis of Variance (ANOVA) to demonstrate that this large-scale climate response is accompanied by significant differences between models in how they respond to the common AMV forcing, particularly in the tropics. These differences may arise from variations in North Atlantic air-sea heat fluxes between models despite a common North Atlantic SST forcing pattern. We cannot detect a widespread effect of increased model horizontal resolution in this climate response, with the exception of the ITCZ, which shifts further northwards in the positive phase of the AMV in the higher resolution configurations.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

TUBB3 Arg262His causes a recognizable syndrome including CFEOM3, facial palsy, joint contractures, and early-onset peripheral neuropathy - Mary C. Whitman; Brenda J. Barry; Caroline D. Robson; Flavia M. Facio; Carol Van Ryzin; Wai-Man Chan; Tanya J. Lehky; Audrey Thurm; Christopher Zalewski; Kelly A. King; Carmen Brewer; Konstantinia Almpani; et al. (Human Genetics, 2021)

Correction to: Evolution and diversity of the angiosperm anther: trends in function and development - Johanna Åstrand; Christopher Knight; Jordan Robson; Behzad Talle; Zoe A. Wilson (Plant Reproduction, 2021)
Unfortunately, the original publication of the article has an error in the labelling on Fig. 3. The correct figure is given in this correction.

Evolution and diversity of the angiosperm anther: trends in function and development - Johanna Åstrand; Christopher Knight; Jordan Robson; Behzad Talle; Zoe A. Wilson (Plant Reproduction, 2021)
Key message Anther development and dehiscence is considered from an evolutionary perspective to identify drivers for differentiation, functional conservation and to identify key questions for future male reproduction research. Abstract Development of viable pollen and its timely release from the anther are essential for fertilisation of angiosperm flowers. The formation and subsequent dehiscence of the anther are under tight regulatory control, and these processes are remarkably conserved throughout the diverse families of the angiosperm clade. Anther development is a complex process, which requires timely formation and communication between the multiple somatic anther cell layers (the epidermis, endothecium, middle layer and tapetum) and the developing pollen. These layers go through regulated development and selective degeneration to facilitate the formation and ultimate release of the pollen grains. Insight into the evolution and divergence of anther development and dehiscence, especially between monocots and dicots, is driving greater understanding of the male reproductive process and increased, resilient crop yields. This review focuses on anther structure from an evolutionary perspective by highlighting their diversity across plant species. We summarise new findings that illustrate the complexities of anther development and evaluate how they challenge established models of anther form and function, and how they may help to deliver future sustainable crop yields.

Substantial long‐term loss of alpha and gamma diversity of lake invertebrates in a landscape exposed to a drying climate - S. T. Atkinson; D. Cale; A. Pinder; J. M. Chambers; S. A. Halse; Belinda J. Robson (Global Change Biology, 2021)
Many regions across the globe are shifting to more arid climates. For shallow lakes, decreasing rainfall volume and timing, changing regional wind patterns and increased evaporation rates alter water regimes so that dry periods occur more frequently and for longer. Drier conditions may affect fauna directly and indirectly through altered physicochemical conditions in lakes. Although many studies have predicted negative effects of such changes on aquatic biodiversity, empirical studies demonstrating these effects are rare. Global warming has caused severe climatic drying in southwestern Australia since the 1970s, so we aimed to determine whether lakes in this region showed impacts on lake hydroperiod, water quality, and α, β and γ diversity of lake invertebrates from 1998 to 2011. Seventeen lakes across a range of salinities were sampled biennially in spring in the Wheatbelt and Great Southern regions of Western Australia. Multivariate analyses were used to identify changes in α, β and γ diversity and examine patterns in physicochemical data. Salinity and average rainfall partially explained patterns in invertebrate richness and assemblage composition. Climatic drying was associated with significant declines in lake depth, increased frequency of dry periods, and reduced α and γ diversity (γ declined from ~300 to ~100 taxa from 1998 to 2011 in the 17 wetlands). In contrast, β diversity remained consistently high, because each lake retained a distinct fauna. Mean α diversity per‐lake declined both in lakes that dried and lakes that did not dry out, but lakes which retained a greater proportion of their maximum depth retained more α diversity. Accumulated losses in α diversity caused the decline in γ diversity likely through shrinking habitat area, fewer stepping stones for dispersal and loss of specific habitat types. Biodiversity loss is thus likely from lakes in drying regions globally. Management actions will need to sustain water depth in lakes to prevent biodiversity loss.

The success of the Montreal Protocol in mitigating interactive effects of stratospheric ozone depletion and climate change on the environment - Paul W. Barnes; Janet F. Bornman; Krishna K. Pandey; Germar H. Bernhard; Alkiviadis F. Bais; Rachel E. Neale; Thomas Matthew Robson; Patrick J. Neale; Craig E. Williamson; Richard G. Zepp; Sasha Madronich; Stephen R. Wilson; et al. (Global Change Biology, 2021)

Life History and Ecology of Bluenose Warehou (Hyperoglyphe antarctica, Centrolophidae) in the Southern Atlantic - James B. Bell; Vladimir Laptikhovsky; David K. A. Barnes; Ramon Benedet; Amelia E. Bridges; James Glass; Warren Glass; Rodney Green; Simon A. Morley; Simon Robertson; Georgia R. Robson; Harry Stanton; et al. (Frontiers in Marine Science, 2021)
Bluenose warehou ( Hyperoglyphe antarctica ) is a popular commercial fish in Australia and New Zealand, but its biology and ecology are very poorly known in other regions where it is found. We present here the first life history data for this species from the south Atlantic, focusing upon the exclusive economic zone (EEZ) of the United Kingdom Overseas Territory (UKOT) of Tristan da Cunha (TdC). Here, bluenose is known from several seamounts and island margins, typically occurring in waters between 200 and 1,000 m depth and is the target species of trawl and longline fishery operating since 1997. We use a suite of methods to describe important life history parameters, including length-weight and age-length relationships and size at recruitment, as well as examining commercial longline survey data to uncover habitat preferences of bluenose. This work has formed an important part of the United Kingdom government’s Blue Belt Program in TdC. It has underpinned the development of the first stock assessment for this species in the Atlantic, as well as a range of improved conservation measures for some of the more vulnerable species that occur in these areas, including seabirds and cold-water corals.

Carbapenem-Resistant Pseudomonas aeruginosa in Chronic Lung Infection: Current Resistance Profile and Hypermutability in Patients with Cystic Fibrosis - Mila M. Almeida; Meyvianne T. Freitas; Tania W. Folescu; Monica C. Firmida; Ana Paula D’A. Carvalho-Assef; Elizabeth A. Marques; Robson S. Leão (Current Microbiology, 2021)

Localization of angiotensin-(1-7) and Mas receptor in the rat ovary throughout the estrous cycle - Virginia M. Pereira; Fernando M. Reis; Geovanni D. Cassali; Sergio H. S. Santos; Maira Casalechi; Robson A. S. Santos; Adelina M. Reis (Journal of Molecular Histology, 2020)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Volatile and semi-volatile components of jetsam ambergris - Michael J. Wilde; William J. Robson; Paul A. Sutton; Steven J. Rowland (Natural Product Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Seroprevalence and risk factors associated with equineleptospirosis in the metropolitan region of Salvador and Recôncavo Baiano region, Bahia state (NE Brazil) - Cândida C. Siqueira; Deborah B. M. Fraga; Adenizar D. Chagas-Junior; Daniel A. Athanazio; Marta M. N. Silva; Robson B. Cerqueira; Flávia W. da C. McBride; Melissa H. Pinna; Maria C. C. Ayres (Tropical Animal Health and Production, 2020)

Comparative larval ontogeny of two fish species (Characiformes and Siluriformes) endemic to the São Francisco River in Brazil - Maíra S. A. Rocha; Robson C. Silva; José C. E. Santos; Marianne Schorer; Maria P. Nascimento; Marcelo M. Pedreira (Journal of Fish Biology, 2020)
The aim of the present study was to perform comparative histological analyses of the ontogenetic development of two fish species endemic to the São Francisco River in Brazil: Prochilodus argenteus and Lophiosilurus alexandri . Histological analyses were performed every 24 h from the moment of hatching until 14 days post‐hatching (dph) for the observation of larval development and until 39 dph for the observation of gonadal development. Whole larvae were fixed in Bouin's solution and the histological slides were stained with haematoxylin–eosin. Lophiosilurus alexandri larvae had a larger body size compared with P. argenteus larvae since hatching. Lophiosilurus alexandri larvae had mouth opening and pigmentation of the eyes upon hatching, whereas these events were observed at 1 dph in P. argenteus larvae. The visualisation and the inflation of the swim bladder occurred at 1 and 3 dph, respectively, in the P. argenteus , whereas these events occurred at 2 and 8 dph, respectively, in L. alexandri . Yolk granules were absorbed at 4 dph in P. argenteus and the 10 dph in L. alexandri . At 7 dph, the digestive tube was more differentiated in L. alexandri than P. argenteus and at 14 dph, the digestive system of both species had features of their eating habits: broad stomach and short intestine in L. alexandri , typical of carnivorous habits; stomach with a mechanical function and long intestine in P. argenteus , typical of detritivorous habits. The epithelial lining tissue, formed by a single layer of cells in the newly hatched larvae (0 dph), differentiated throughout the study, exhibiting scales in P. argenteus and numerous club cells in the middle epithelial region of L. alexandri at 39 dph. Undifferentiated gonads with somatic cells and primordial germ cells were observed at 39 dph, with caudal‐cranial migration since 1 dph in both species. The anatomic changes during the ontogeny of P. argenteus and L. alexandri larvae are directly associated with the evolutionary history of each species, which explains their feeding habits, behaviour and distribution in the environment: Prochilodus argenteus is detritivorous and actively swims in the water column, whereas L. alexandri is carnivorous and inhabits bottom regions. At 39 dph neither species exhibited sexual differentiation.

Estimation of fruit load in mango orchards: tree sampling considerations and use of machine vision and satellite imagery - N. T. Anderson; J. P. Underwood; M. M. Rahman; A. Robson; K. B. Walsh (Precision Agriculture, 2019)

Potential of Solanum viarum Dunal in use for phytoremediation of heavy metals to mining areas, southern Brazil - Thays França Afonso; Carolina Faccio Demarco; Simone Pieniz; Flávio A. O. Camargo; Maurízio Silveira Quadro; Robson Andreazza (Environmental Science and Pollution Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Is thermal limitation the primary driver of elevational distributions? Not for montane rainforest ants in the Australian Wet Tropics - Somayeh Nowrouzi; Alan N. Andersen; Tom R. Bishop; Simon K. A. Robson (Oecologia, 2018)

In situ phytoremediation characterization of heavy metals promoted by Hydrocotyle ranunculoides at Santa Bárbara stream, an anthropogenic polluted site in southern of Brazil - Carolina F. Demarco; Thays F. Afonso; Simone Pieniz; Maurízio S. Quadro; Flávio A. O. Camargo; Robson Andreazza (Environmental Science and Pollution Research, 2018)

Distinct roles of ecto-nucleoside triphosphate diphosphohydrolase-2 (NTPDase2) in liver regeneration and fibrosis - Linda Feldbrügge; Z. Gordon Jiang; Eva Csizmadia; Shuji Mitsuhashi; Stephanie Tran; Eric U. Yee; Sonja Rothweiler; Kahini A. Vaid; Jean Sévigny; Moritz Schmelzle; Yury V. Popov; Simon C. Robson (Purinergic Signalling, 2018)

Kinin Receptors Sensitize TRPV4 Channel and Induce Mechanical Hyperalgesia: Relevance to Paclitaxel-Induced Peripheral Neuropathy in Mice - Robson Costa; Maíra A. Bicca; Marianne N. Manjavachi; Gabriela C. Segat; Fabiana Chaves Dias; Elizabeth S. Fernandes; João B. Calixto (Molecular Neurobiology, 2018)

Potential role of P2X7R in esophageal squamous cell carcinoma proliferation - André A Santos; Angélica R Cappellari; Fernanda O de Marchi; Marina P Gehring; Aline Zaparte; Caroline A Brandão; Tiago Giuliani Lopes; Vinicius D da Silva; Luis Felipe Ribeiro Pinto; Luiz Eduardo Baggio Savio; Aline Cristina Abreu Moreira-Souza; Robson Coutinho-Silva; et al. (Purinergic Signalling, 2017)

Bj-PRO-5a and Bj-PRO 10c Found at C-Type Natriuretic Peptide Precursor of Bothrops jararaca Change Renal Function of Hypertensive Rats - Carlos H. Xavier; José Rodolfo R. Miranda; Juliana Yamaguchi; Kátia D. da Silveira; Mauro M. Teixeira; Deoclécio Alves Chianca-Jr; Ana C. Simões e Silva; Robson A. S. Santos; Antônio C. M. Camargo; Danielle Ianzer (International Journal of Peptide Research and Therapeutics, 2017)

Structural evolution of a normal fault array in the Gambier Embayment, offshore Otway Basin, South Australia: insights from 3D seismic data - A. G. Robson; S. P. Holford; R. C. King (Australian Journal of Earth Sciences, 2017)

Use of Particle Tracking to Determine Optimal Release Dates and Locations for Rehabilitated Neonate Sea Turtles - Natalie A. Robson; Yasha Hetzel; Scott Whiting; Sarath Wijeratne; Charitha B. Pattiaratchi; Philip Withers; Michele Thums (Frontiers in Marine Science, 2017)

Planning and management for sustainable coastal aquaculture development in Santa Catarina State, south Brazil - Felipe M. Suplicy; Luiz F. de Novaes Vianna; Guilherme S. Rupp; André L. T. Novaes; Luis H. P. Garbossa; Robson V. de Souza; João Guzenski; Sérgio W. da Costa; Fabiano M. Silva; Alex A. dos Santos (Reviews in Aquaculture, 2017)
Marine aquaculture of bivalve molluscs is an important economic activity in Santa Catarina State, Brazil, with more than 5000 persons directly and indirectly involved and an annual revenue of US $ 18 million in 2013. In the first decade of this activity, a lack of proper regulation imposed multiple obstacles to the sustainable management of local shellfish farming. The occupation of marine space occurred in a disorderly manner, and the unplanned development led to unfavourable conditions that threatened the sustainability of the industry. This study describes how better planning and management tools have improved governance of marine aquaculture in Santa Catarina State. The process included development of a legal framework for aquaculture planning, elaboration of local development plans with a participatory and multidisciplinary approach, development of a geographic information system to identify favourable areas and creation of a Web‐based aquaculture management system. The combined application of these actions, along with continuing extension services, is expected to contribute to the regulation of 837 shellfish farming areas, the expansion of farming activity, the mitigation of the environmental and visual impacts caused by coastal aquaculture and an increase in the public health of shellfish consumers. In this manuscript, we report an example of how the application of better planning and management of the aquaculture sector can prepare the industry for a sustainable growing cycle.

Modeling What We Sample and Sampling What We Model: Challenges for Zooplankton Model Assessment - Jason D. Everett; Mark E. Baird; Pearse Buchanan; Cathy Bulman; Claire Davies; Ryan Downie; Chris Griffiths; Ryan Heneghan; Rudy J. Kloser; Leonardo Laiolo; Ana Lara-Lopez; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2017)

Cu(II) adsorption from copper mine water by chitosan films and the matrix effects - Tuanny S. Frantz; Nauro Silveira; Maurízio S. Quadro; Robson Andreazza; Amauri A. Barcelos; Tito R. S. Cadaval; Luiz A. A. Pinto (Environmental Science and Pollution Research, 2017)

Thermotolerant coliform loadings to coastal areas of Santa Catarina (Brazil) evidence the effect of growing urbanisation and insufficient provision of sewerage infrastructure - Luis H. P. Garbossa; Robson V. Souza; Carlos J. A. Campos; Argeu Vanz; Luiz F. N. Vianna; Guilherme S. Rupp (Environmental Monitoring and Assessment, 2017)

Decadal predictions with the HiGEM high resolution global coupled climate model: description and basic evaluation - L. C. Shaffrey; D. Hodson; J. Robson; D. P. Stevens; E. Hawkins; I. Polo; I. Stevens; R. T. Sutton; G. Lister; A. Iwi; D. Smith; A. Stephens (Climate Dynamics, 2017)

Division of labor in complex societies: a new age of conceptual expansion and integrative analysis - Simon K. A. Robson; James F. A. Traniello (Behavioral Ecology and Sociobiology, 2016)

Exploring, exploiting and evolving diversity of aquatic ecosystem models: a community perspective - Annette B. G. Janssen; George B. Arhonditsis; Arthur Beusen; Karsten Bolding; Louise Bruce; Jorn Bruggeman; Raoul-Marie Couture; Andrea S. Downing; J. Alex Elliott; Marieke A. Frassl; Gideon Gal; Daan J. Gerla; et al. (Aquatic Ecology, 2015)

Population pharmacokinetic analysis of oseltamivir and oseltamivir carboxylate following intravenous and oral administration to patients with and without renal impairment - Leonid Gibiansky; Mylène Giraudon; Craig R. Rayner; Barbara J. Brennan; Vishak Subramoney; Richard Robson; Mohamed A. Kamal (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Assessing the response of plant flavonoids to UV radiation: an overview of appropriate techniques - Riitta Julkunen-Tiitto; Nikolaos Nenadis; Susanne Neugart; Matthew Robson; Giovanni Agati; Jouko Vepsäläinen; Gaetano Zipoli; Line Nybakken; Barbro Winkler; Marcel A. K. Jansen (Phytochemistry Reviews, 2015)

The interactions between temperature and activity levels in driving metabolic rate: theory, with empirical validation from contrasting ectotherms - L. G. Halsey; P. G. D. Matthews; E. L. Rezende; L. Chauvaud; A. A. Robson (Oecologia, 2015)

Evolutionary transitions of complex labile traits: Silk weaving and arboreal nesting in Polyrhachis ants - Simon K. A. Robson; Rudy J. Kohout; Andrew T. Beckenbach; Corrie S. Moreau (Behavioral Ecology and Sociobiology, 2015)

Phytoplankton spatial distribution on the Continental Shelf off Rio de Janeiro, from Paraíba do Sul River to Cabo Frio - Gleyci A. O. Moser; Robson Alves Takanohashi; Mariana de Chagas Braz; Domênica Teixeira de Lima; Fabiana Vasconcelos Kirsten; Josefa Varela Guerra; Alexandre M. Fernandes; Ricardo César Gonçalves Pollery (Hydrobiologia, 2014)

Oral administration of angiotensin-(1–7) ameliorates type 2 diabetes in rats - Sérgio H. S. Santos; Jorge F. Giani; Valeria Burghi; Johanna G. Miquet; Fatimunnisa Qadri; Janaina F. Braga; Mihail Todiras; Katarina Kotnik; Natalia Alenina; Fernando P. Dominici; Robson A. S. Santos; Michael Bader (Journal of Molecular Medicine, 2014)

Biodegradation of starch blended polyvinyl chloride films by isolated Phanerochaete chrysosporium PV1 - M. I. Ali; S. Ahmed; I. Javed; N. Ali; N. Atiq; A. Hameed; G. Robson (International Journal of Environmental Science and Technology, 2014)

Development and application of a molecular sexing protocol in the climate change-sensitive American pika - Clayton T. Lamb; Kelsey M. Robson; Michael A. Russello (Conservation Genetics Resources, 2014)

The equine CD1 gene family is the largest and most diverse yet identified - Robson G. Dossa; Debra C. Alperin; Melissa T. Hines; Stephen A. Hines (Immunogenetics, 2014)

Menstrual and reproductive characteristics and breast density in young women - Joanne F. Dorgan; Catherine Klifa; Snehal Deshmukh; Brian L. Egleston; John A. Shepherd; Peter O. Kwiterovich; Linda Van Horn; Linda G. Snetselaar; Victor J. Stevens; Alan M. Robson; Norman L. Lasser; Nola M. Hylton (Cancer Causes & Control, 2013)

Comparative evaluation of different preservation methods for cyanobacterial strains - Alberto A. Esteves-Ferreira; Débora M. Corrêa; Antônio P. S. Carneiro; Rinamara M. Rosa; Robson Loterio; Wagner L. Araújo (Journal of Applied Phycology, 2013)

Biosorption and Bioreduction of Copper from Different Copper Compounds in Aqueous Solution - Robson Andreazza; Benedict C. Okeke; Simone Pieniz; Fátima M. Bento; Flávio A. O. Camargo (Biological Trace Element Research, 2013)

Tissue specific localization of angiotensin-(1–7) and its receptor Mas in the uterus of ovariectomized rats - João Vaz-Silva; Rubens L. Tavares; Márcia C. Ferreira; Kinulpe Honorato-Sampaio; Ines K. D. Cavallo; Robson A. S. Santos; Adelina M. dos Reis; Fernando M. Reis (Journal of Molecular Histology, 2012)

Trabecular Level Analysis of Bone Cement Augmentation: A Comparative Experimental and Finite Element Study - Y. Zhao; K. A. Robson Brown; Z. M. Jin; R. K. Wilcox (Annals of Biomedical Engineering, 2012)

Overexpression of NTPDase2 in gliomas promotes systemic inflammation and pulmonary injury - Elizandra Braganhol; Rafael F. Zanin; Andressa Bernardi; Leticia S. Bergamin; Angelica R. Cappellari; Luis F. Campesato; Fernanda B. Morrone; Maria M. Campos; João B. Calixto; Maria Isabel A. Edelweiss; Márcia R. Wink; Jean Sévigny; et al. (Purinergic Signalling, 2012)

Characterization of Copper-Resistant Rhizosphere Bacteria from Avena sativa and Plantago lanceolata for Copper Bioreduction and Biosorption - Robson Andreazza; Benedict C. Okeke; Simone Pieniz; Flávio A. O. Camargo (Biological Trace Element Research, 2012)

Effects of Stimulation of Copper Bioleaching on Microbial Community in Vineyard Soil and Copper Mining Waste - Robson Andreazza; Benedict C. Okeke; Simone Pieniz; Leandro Bortolon; Márcio R. Lambais; Flávio A. O. Camargo (Biological Trace Element Research, 2012)

Synthesis and Pharmacological Characterization of a Novel Sigma Receptor Ligand with Improved Metabolic Stability and Antagonistic Effects Against Methamphetamine - Michael J. Seminerio; Matthew J. Robson; Ahmed H. Abdelazeem; Christophe Mesangeau; Seshulatha Jamalapuram; Bonnie A. Avery; Christopher R. McCurdy; Rae R. Matsumoto (The AAPS Journal, 2012)

Diet of juvenile green turtles (Chelonia mydas) associating with artisanal fishing traps in a subtropical estuary in Brazil - Shany Mayumi Nagaoka; Agnaldo Silva Martins; Robson Guimarães dos Santos; Mônica Maria Pereira Tognella; Eurico Cabral de Oliveira Filho; Jeffrey A. Seminoff (Marine Biology, 2012)

Colony genetic structure in the Australian jumper ant Myrmecia pilosula - Z.-Q. Qian; B. C. Schlick-Steiner; F. M. Steiner; S. K. A. Robson; H. Schlüns; E. A. Schlüns; R. H. Crozier (Insectes Sociaux, 2012)

Potential Phytoextraction and Phytostabilization of Perennial Peanut on Copper-Contaminated Vineyard Soils and Copper Mining Waste - Robson Andreazza; Leandro Bortolon; Simone Pieniz; Marcelo Giacometti; Dione D. Roehrs; Mácio R. Lambais; Flávio A. O. Camargo (Biological Trace Element Research, 2011)

Prednisolone treatment reduces endometrial spiral artery development in women with recurrent miscarriage - Gendie E. Lash; Judith N. Bulmer; Barbara A. Innes; Josephine A. Drury; Stephen C. Robson; Siobhan Quenby (Angiogenesis, 2011)

Bioreduction of Cu(II) by Cell-Free Copper Reductase from a Copper Resistant Pseudomonas sp. NA - Robson Andreazza; Benedict C. Okeke; Simone Pieniz; Adriano Brandelli; Mácio R. Lambais; Flávio A. O. Camargo (Biological Trace Element Research, 2011)

Synthesis and Pharmacological Evaluation of 6-Acetyl-3-(4-(4-(4-fluorophenyl)piperazin-1-yl)butyl)benzo[d]oxazol-2(3H)-one (SN79), a Cocaine Antagonist, in Rodents - Nidhi Kaushal; Matthew J. Robson; Harsha Vinnakota; Sanju Narayanan; Bonnie A. Avery; Christopher R. McCurdy; Rae R. Matsumoto (The AAPS Journal, 2011)

Late Neogene tectonics in northwestern Victoria: Evidence from the Late Miocene–Pliocene Loxton Sand - T. C. Robson; J. A. Webb (Australian Journal of Earth Sciences, 2011)

Impact of CD39 and purinergic signalling on the growth and metastasis of colorectal cancer - Beat M. Künzli; Maria-Isabell Bernlochner; Stephan Rath; Samuel Käser; Eva Csizmadia; Keiichi Enjyoji; Peter Cowan; Anthony d’Apice; Karen Dwyer; Robert Rosenberg; Aurel Perren; Helmut Friess; et al. (Purinergic Signalling, 2011)

A flexible quantitative methodology for the analysis of gene-flow between conventionally bred maize populations using microsatellite markers - P. R. H. Robson; R. Kelly; E. F. Jensen; G. D. Giddings; M. Leitch; C. Davey; A. P. Gay; G. Jenkins; H. Thomas; I. S. Donnison (Theoretical and Applied Genetics, 2011)

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Effect of anthropogenic feeding regimes on activity rhythms of laboratory mussels exposed to natural light - Anthony A. Robson; Carlos Garcia de Leaniz; Rory P. Wilson; Lewis G. Halsey (Hydrobiologia, 2010)

The reliability of the IL-6, sIL-6R and sgp130 response to a preloaded time trial - I. Walshe; P. Robson-Ansley; A. St Clair Gibson; C. Lawrence; K. G. Thompson; L. Ansley (European Journal of Applied Physiology, 2010)

Improved detection following Neuro-Eye Therapy in patients with post-geniculate brain damage - Arash Sahraie; Mary-Joan MacLeod; Ceri T. Trevethan; Siân E. Robson; John A. Olson; Paula Callaghan; Brigitte Yip (Experimental Brain Research, 2010)

Weaver ants Oecophylla smaragdina encounter nasty neighbors rather than dear enemies - Philip S. Newey; Simon K. A. Robson; Ross H. Crozier (Ecology, 2010)
The evolution of territorial behavior requires that the benefits of territoriality outweigh the costs. The costs are primarily those of territorial defense against encroaching neighbors or against floaters seeking to establish their own territory. One way to reduce the cost of defense might be to restrict serious conflict to encounters with those posing the greatest threat. Studies of many animals have found that less aggression is shown toward neighbors than toward strangers, a phenomenon known as the “dear enemy” effect. However, the opposite can also be true, namely, that more aggression is shown toward neighbors than strangers: the “nasty neighbor” effect. This may be particularly true of group‐living species that defend a resource‐based territory. Here we show that (1) colonies of the weaver ant Oecophylla smaragdina were able to recognize a greater proportion of workers from neighboring colonies as non‐colony members; and (2) when recognized as non‐colony members, more aggression was exhibited toward neighbors than non‐neighbors. We present for the first time evidence that differential levels of aggression involve both a perceptual and behavioral component. On the other hand, we found no evidence that weaver ant workers were better able to recognize workers from previously unknown colonies or responded more aggressively to them, even after a 10‐day period of contact. This contrasts with other species in which rapid learning of the identity of new potential enemies has been demonstrated. We suggest that such a response is unnecessary for weaver ants, as encounters with intruders from non‐neighboring colonies are probably rare and of little consequence. This study adds to the growing body of evidence that the nasty neighbor effect may be much more common than the dear enemy effect among group‐living species.

Angiotensin (1–7) and its receptor Mas are expressed in the human testis: implications for male infertility - Augusto B. Reis; Fabiano C. Araújo; Virginia M. Pereira; Adelina M. Dos Reis; Robson A. Santos; Fernando M. Reis (Journal of Molecular Histology, 2010)

Ants as indicators for vertebrate fauna at a local scale: an assessment of cross-taxa surrogacy in a disturbed matrix - J. M. Bennett; A. S. Kutt; C. N. Johnson; S. K. A. Robson (Biodiversity and Conservation, 2009)

Heightened NTPDase-1/CD39 expression and angiogenesis in radiation proctitis - Sunil Sheth; Wissam Bleibel; Chandrashekhar Thukral; Yousif A-Rahim; Guido Beldi; Eva Csizmadia; Simon C. Robson (Purinergic Signalling, 2009)

Nest and colony-specific spectra in the weaver ant Oecophylla smaragdina - P. Newey; S. K. A. Robson; R. H. Crozier (Insectes Sociaux, 2009)

The effect of surface colour on the adhesion strength of Elminius modestus Darwin on a commercial non-biocidal antifouling coating at two locations in the UK - Martha A. Robson; David Williams; Kirsten Wolff; Jeremy C. Thomason (Biofouling, 2009)

Breeding system, colony and population structure in the weaver ant Oecophylla smaragdina - E.A. SCHLÜNS; B.J. WEGENER; H. SCHLÜNS; N. AZUMA; S. K. A. ROBSON; R. H. CROZIER (Molecular Ecology, 2009)
Weaver ants ( Oecophylla smaragdina ) are dominant ants in open forests from India, Australia, China and Southeast Asia, whose leaf nests are held together with larval silk. The species, together with its sole congener O. longinoda , has been important in research on biological control, communication, territoriality and colony integration. Over most of the range, only one queen has been found per colony, but the occurrence of several queens per nest has been reported for the Australian Northern Territory. The number of males mating with each queen is little known. Here we report on the colony structure of O. smaragdina using published and new microsatellite markers. Worker genotype arrays reflect the occurrence of habitual polygyny (more than one queen per colony) in 18 colonies from Darwin, Northern Australia, with up to five queens inferred per colony. Monogyny (one queen per colony) with occasional polygyny was inferred for 14 colonies from Queensland, Australia, and 20 colonies from Java, Indonesia. Direct genotyping of the sperm carried by 77 Queensland queens and worker genotypic arrays of established colonies yielded similar results, indicating that less than half of the queens mate only once and some mate up to five times. Worker genotype arrays indicated that queens from Java and the Northern Territory also often mate with more than one male, but less often than those from Queensland. A strong isolation‐by‐distance effect was found for Queensland samples. The variation uncovered means that O. smaragdina is a more versatile study system than previously supposed.

Near-infrared spectroscopy identifies the colony and nest of origin of weaver ants, Oecophylla smaragdina - P. S. Newey; S. K. A. Robson; R. H. Crozier (Insectes Sociaux, 2008)

Fluorescence Modulation of Acridine and Coumarin Dyes by Silver Nanoparticles - Carolina A. Sabatini; Robson V. Pereira; Marcelo H. Gehlen (Journal of Fluorescence, 2007)

Bryophyte dispersal by flying foxes: a novel discovery - J. G. Parsons; A. Cairns; C. N. Johnson; S. K. A. Robson; L. A. Shilton; D. A. Westcott (Oecologia, 2007)

Social and genetic structure of a supercolonial weaver ant, Polyrhachis robsoni, with dimorphic queens - J. S. van Zweden; M. E. Carew; M. T. Henshaw; S. K. A. Robson; R. H. Crozier (Insectes Sociaux, 2007)

Sequencing EVC and EVC2 identifies mutations in two-thirds of Ellis–van Creveld syndrome patients - Stuart W. J. Tompson; Victor L. Ruiz-Perez; Helen J. Blair; Stephanie Barton; Victoria Navarro; Joanne L. Robson; Michael J. Wright; Judith A. Goodship (Human Genetics, 2006)

Effect of Extracellular ATP on the Human Leukaemic Cell Line K562 and its Multidrug Counterpart - Alcira A. Bernardo; Flavio Eduardo Pinto-Silva; Pedro M. Persechini; Robson Coutinho-Silva; José Roberto Meyer-Fernandes; André Luiz Fonseca de Souza; Vivian M. Rumjanek (Molecular and Cellular Biochemistry, 2006)

Decoupling the direct and indirect effects of nitrogen deposition on ecosystem function - Pete Manning; John E. Newington; Helen R. Robson; Mark Saunders; Till Eggers; Mark A. Bradford; Richard D. Bardgett; Michael Bonkowski; Richard J. Ellis; Alan C. Gange; Susan J. Grayston; Ellen Kandeler; et al. (Ecology Letters, 2006)
Elevated nitrogen (N) inputs into terrestrial ecosystems are causing major changes to the composition and functioning of ecosystems. Understanding these changes is challenging because there are complex interactions between ‘direct’ effects of N on plant physiology and soil biogeochemistry, and ‘indirect’ effects caused by changes in plant species composition. By planting high N and low N plant community compositions into high and low N deposition model terrestrial ecosystems we experimentally decoupled direct and indirect effects and quantified their contribution to changes in carbon, N and water cycling. Our results show that direct effects on plant growth dominate ecosystem response to N deposition, although long‐term carbon storage is reduced under high N plant‐species composition. These findings suggest that direct effects of N deposition on ecosystem function could be relatively strong in comparison with the indirect effects of plant community change.

The structure of a micro-bat community in relation to gradients of environmental variation in a tropical urban area - C. L. Hourigan; C. Johnson; S. K. A. Robson (Urban Ecosystems, 2006)

Direct and indirect effects of solar ultraviolet‐B radiation on long‐term decomposition - Verónica A. Pancotto; Osvaldo E. Sala; T. Matthew Robson; Martyn M. Caldwell; Ana L. Scopel (Global Change Biology, 2005)
As a result of stratospheric ozone depletion, more solar ultraviolet‐B radiation (UV‐B, 280–315 nm) is reaching the Earth's surface. Enhanced levels of UV‐B may, in turn, alter ecosystem processes such as decomposition. Solar UV‐B radiation could affect decomposition both indirectly, by changes in the chemical composition of leaves during growth, or directly by photochemical breakdown of litter and through changes in decomposer communities exposed to sunlight. In this experiment, we studied indirect and direct effects of solar UV‐B radiation on decomposition of barley ( Hordeum vulgare ). We used barley straw and leaf litter grown under reduced UV‐B (20% of ambient UV‐B) or under near‐ambient UV‐B (90% of ambient UV‐B) in Buenos Aires, Argentina, and decomposed the litter under reduced or near‐ambient solar UV‐B for 29 months in Tierra del Fuego, Argentina. We found that the UV‐B treatment applied during growth decreased the decay rate. On the other hand, there was a marginally significant direct effect of elevated UV‐B during the early stages of decomposition, suggesting increased mass loss. The effect of UV‐B during growth on decomposition was likely the result of changes in plant litter chemical composition. Near‐ambient UV‐B received during plant growth decreased the concentrations of nitrogen, soluble carbohydrates, and N/P ratio, and increased the concentrations of phosphorus, cellulose, UV‐B‐absorbing compounds, and lignin/N ratio. Thus, solar UV‐B radiation affects the decomposition of barley litter directly and indirectly, and indirect effects are persistent for the whole decomposition period.

Immature Steller sea lion ( Eumetopias jubatus ) dive activity in relation to habitat features of the eastern Aleutian Islands - BRIAN S. FADELY; BRUCE W. ROBSON; JEREMY T. STERLING; ANGIE GREIG; KATHERINE A. CALL (Fisheries Oceanography, 2005)
Current flow and bathymetry in the Aleutian Islands define unique habitats that influence prey distribution and foraging behaviour of top‐level predators. We explored whether oceanographic features and bathymetry influenced the diving activity of 30 immature sea lions (ages 5–21 months) equipped with satellite‐linked depth recorders in the eastern Aleutian Islands (EAI) during 2000–02. Sea surface temperature (SST) and chlorophyll a concentrations were obtained from remote sensing satellite imagery and associated with locations where sea lion diving was recorded. Most locations associated with diving to >4 m were within 10 nautical miles (nm) of shore and associated with onshelf waters a concentrations, but also with sea lion age. Associations with habitat features did not consistently explain variability in dive count, time at depth, dive focus or focal depth. Nearshore diving tended to be influenced by distance from shore or seafloor depth, whereas increased SST coincided with activity of sea lions diving >30 nm offshore. Immature sea lions developing into independent foragers in the relatively shallow pass areas of the EAI do so at a time of rapid changes in oceanography and prey availability.

Comparative hydrolysis of P2 receptor agonists by NTPDases 1, 2, 3 and 8 - F. Kukulski; S. A. Lévesque; É. G. Lavoie; J. Lecka; F. Bigonnesse; A. F. Knowles; S. C. Robson; T. L. Kirley; J. Sévigny (Purinergic Signalling, 2005)

Indigenous and introduced arbuscular mycorrhizal fungi contribute to plant growth in two agricultural soils from south-western Australia - C. Gazey; L. K. Abbott; A. D. Robson (Mycorrhiza, 2004)

The origin and spread of the HFE-C282Y haemochromatosis mutation - S. Distante; K.J.H. Robson; J. Graham-Campbell; A. Arnaiz-Villena; P. Brissot; Mark Worwood (Human Genetics, 2004)

Reduction of solar UV-B mediates changes in the Sphagnum capitulum microenvironment and the peatland microfungal community - T. Matthew Robson; Verónica A. Pancotto; Carlos L. Ballaré; Osvaldo E. Sala; Ana L. Scopel; Martyn M. Caldwell (Oecologia, 2004)

Modification of senescence in ryegrass transformed with IPT under the control of a monocot senescence-enhanced promoter - Q. Li; P. R. H. Robson; A. J. E. Bettany; I. S. Donnison; H. Thomas; I. M. Scott (Plant Cell Reports, 2004)

Queen number, queen cycling and queen loss: the evolution of complex multiple queen societies in the social wasp genus Ropalidia - Michael T. Henshaw; Simon K. A. Robson; Ross H. Crozier (Behavioral Ecology and Sociobiology, 2004)

Angiotensin-(1–7) stimulates water transport in rat inner medullary collecting duct: evidence for involvement of vasopressin V2 receptors - Antonio J. Magaldi; Katia R. Cesar; Magali de Araújo; Ana C. Simões e Silva; Robson A. S. Santos (Pflügers Archiv - European Journal of Physiology, 2003)

Solar UV‐B decreases decomposition in herbaceous plant litter in Tierra del Fuego, Argentina: potential role of an altered decomposer community - Verónica A. Pancotto; Osvaldo E. Sala; Marta Cabello; Nancy I. López; T. Matthew Robson; Carlos L. Ballaré; Martyn M. Caldwell; Ana L. Scopel (Global Change Biology, 2003)
Tierra del Fuego, Argentina (55°S), receives increased solar ultraviolet‐B radiation (UV‐B) as a result of Antarctic stratospheric ozone depletion. We conducted a field study to examine direct and indirect effects of solar UV‐B radiation on decomposition of Gunnera magellanica , a native perennial herb, and on the native community of decomposer organisms. In general, indirect effects of UV‐B mostly occur due to changes in the chemical composition of litter, whereas direct effects during decomposition result from changes in decomposer organisms and/or differences in the photochemical breakdown of litter. We designed a full‐factorial experiment using senescent leaves that had received either near‐ambient or attenuated UV‐B during growth. The leaves were distributed in litterbags and allowed to decompose under near‐ambient or reduced solar UV‐B during the growing season. We evaluated initial litter quality, mass loss, and nutrient release of decomposing litter, and microbial colonization of both initial litter and decomposed litter. We found that litter that decomposed under near‐ambient UV‐B had significantly less mass loss than litter that decomposed under reduced UV‐B. The UV‐B conditions received by plants during growth, which did not affect mass loss and nutrient composition of litter, affected fungal species composition but in different ways throughout the decomposition period. Before the decomposition trial, Beauveria bassiana and Penicillium frequentans were higher under reduced UV‐B, whereas Cladosporium herbarum and pigmented bacteria were more common under the near‐ambient compared to the reduced UV‐B treatment. After the decomposition period, leaves that had grown under reduced UV‐B showed higher frequency of Penicillium thomii and lower frequency of Trichoderma polysporum than leaves that had grown under near‐ambient conditions. The UV‐B condition received during decomposition also affected fungal colonization, with Penicillium chrysogenum being more frequent in leaves that had decomposed under reduced UV‐B, while the other species were not affected. Our results demonstrate that, in this ecosystem, the effects of UV‐B radiation on decomposition apparently occurred mostly through changes in the fungal community, while changes in photochemical breakdown appeared to be less important.

A hypertonicity-activated nonselective conductance in single proximal tubule cells isolated from mouse kidney - K. J. D. Balloch; J. A. Hartley; I. D. Millar; J. D. Kibble; L. Robson (The Journal of Membrane Biology, 2003)

The formation, morphology and anatomy of cluster root of Lupinus albus L. as dependent on soil type and phosphorus supply - C. S. Peek; A. D. Robson; J. Kuo (Plant and Soil, 2003)

Appropriate choice of antibiotic and Agrobacterium strain improves transformation of antibiotic-sensitive Fragaria vesca and F. v. semperflorens - M. Alsheikh; H.-P. Suso; M. Robson; N. Battey; A. Wetten (Plant Cell Reports, 2002)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Cultivar variation in the effect of chlorsulfuron in depressing the uptake of copper in wheat - C. Tang; A. D. Robson (Plant and Soil, 2000)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Evaluation of methylation analysis for diagnostic testing in 258 referrals suspected of Prader-Willi or Angelman syndromes - Tina Buchholz; Julianne Jackson; Lisa Robson; A. Smith (Human Genetics, 1998)

Stormwater impact to the freshwater Savannas Preserve marsh, Florida, USA - Gregory A. Graves; Douglas G. Strom; Bill E. Robson (Hydrobiologia, 1998)

The effect of severe eccentric exercise-induced muscle damage on plasma elastase, glutamine and zinc concentrations - M. Gleeson; N. P. Walsh; A. K. Blannin; P. J. Robson; L. Cook; A. E. Donnelly; S. H. Day (European Journal of Applied Physiology, 1998)

The effects of high-intensity intermittent exercise on the plasma concentrations of glutamine and organic acids - N. P. Walsh; A. K. Blannin; A. M. Clark; L. Cook; P. J. Robson; M. Gleeson (European Journal of Applied Physiology, 1998)

Resource Assessment, Recruitment Behavior, and Organization of Cooperative Prey Retrieval in the Ant Formica schaufussi (Hymenoptera: Formicidae) - Simon K. Robson; James F. A. Traniello (Journal of Insect Behavior, 1998)

Effect of phosphorus supply on periplasmic protein profiles in Rhizobia - J. B. Smart; M. J. Dilworth; A. D. Robson (Archives of Microbiology, 1984)

Effect of phosphorus supply on phosphate uptake and alkaline phosphatase activity in Rhizobia - J. B. Smart; M. J. Dilworth; A. D. Robson (Archives of Microbiology, 1984)

A continuous culture study of the phosphorus nutrition of Rhizobium trifollii WU95, Rhizobium NGR234 and Bradyrhizobium CB756 - J. B. Smart; A. D. Robson; M. J. Dilworth (Archives of Microbiology, 1984)